Morphometric analysis of spiny lobster (Panulirus penicillatus) and bamboo lobster (Panulirus versicolor) in Sabang Waters - Iqbal Muhammad; Abdullah Abbas Muhammadar; Firdus Firdus; Sari Widya (BIO Web of Conferences, 2024)
This research aims to analyze morphometrics of (P. penicillatus) and (P. versicolor) in waters of Sabang. A total of 50 samples from each species of P. penicillatus and P. versicolor were used for morphometric analysis using Traditional Morphometric and Truss Morphometric approaches. Morphological analysis indicated that both lobster species are categorized into two distinct groups. Traditional morphometric character testing using ANOVA showed that species differences significantly influence the variation in morphological characters (P<0.05) in both lobsters. Further Duncan post hoc tests revealed that four characters (HL), (CHW), and (CHL)) differed significantly between the species. P. penicillatus shared three characters similar to P. versicolor, namely (HL), (CHW), and (CHL). This similarity is based on the shape of HL, CHW, and CHL in both lobsters. In the Truss Morphometric character testing with ANOVA, it was found that species differences affect the characters significantly (P<0.05). The Duncan post hoc test revealed that five characters ([A1, A3], [B1, B3], [C5, C6], D4, [D5, D6]) differed significantly between species. DFA resulted in 1 function, with an eigenvalue of 27.595, indicating that it explains 100% of the total variance. The morphological characters that significantly contribute to the differentiation between species are A1, B1, C5, A5, and D5.